2002
DOI: 10.1002/art.10509
|View full text |Cite
|
Sign up to set email alerts
|

Association of mutations in the NALP3/CIAS1/PYPAF1 gene with a broad phenotype including recurrent fever, cold sensitivity, sensorineural deafness, and AA amyloidosis

Abstract: Objective. Familial cold urticaria (FCU) andMuckle-Wells syndrome (MWS) are dominantly inherited autoinflammatory disorders that cause rashes, fever, arthralgia, and in some subjects, AA amyloidosis, and have been mapped to chromosome 1q44. Sensorineural deafness in MWS, and provocation of symptoms by cold in FCU, are distinctive features. This study was undertaken to characterize the genetic basis of FCU, MWS, and an overlapping disorder in French Canadian, British, and Indian families, respectively.Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
211
1
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 334 publications
(229 citation statements)
references
References 24 publications
7
211
1
6
Order By: Relevance
“…Alternative splicing of the LRR region is evident for virtually all NALPs as detected by EST analysis and the cloning of various NALPs. 66,67 Moreover, it is interesting to note that exon-exon junctions disrupt the b-strand that is predicted in binding targets. Therefore, alternative splicing not only reorganize the numbers of bstrand but generate completely new b-strands allowing maximal variability in the ligand recognition region.…”
Section: Repertoire and Genomic Organization Of The Nalp Lrrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative splicing of the LRR region is evident for virtually all NALPs as detected by EST analysis and the cloning of various NALPs. 66,67 Moreover, it is interesting to note that exon-exon junctions disrupt the b-strand that is predicted in binding targets. Therefore, alternative splicing not only reorganize the numbers of bstrand but generate completely new b-strands allowing maximal variability in the ligand recognition region.…”
Section: Repertoire and Genomic Organization Of The Nalp Lrrsmentioning
confidence: 99%
“…66,86,87 All three disorders are closely related autoinflammatory syndromes characterized by periodic fever, skin rashes, amyloidosis and in the case of CINCA, the eventual development of neurological complications. Mutations in NALP3 confer a gain of function to the protein, resulting in constitutively active NALP3 in Muckle Wells patients.…”
Section: Nalp3 Inflammasome and Autoinflammatory Disordersmentioning
confidence: 99%
“…69 These pathologies are listed in order of increasing disease severity and life-threatening potential, and are characterized by recurrent episodes of fever, rush, arthropathies and various degrees of neurological complications. [70][71][72] Genetic studies of CAPS identified more than 90 disease-associated genetic variants of the NLRP3 gene, the majority of which are autosomal dominant missense point mutations located in exon 3, encoding the NATCH domain ( Figure 3 and Table 1). 73,74 Despite the familial recurrence, some genetic variants inducing CAPS phenotypes result from de novo mutations.…”
Section: Genetics Of Inflammasomes In Autoinflammatory Diseasesmentioning
confidence: 99%
“…68 Similar analyses have been performed in populations defined by the mutations in genes that are responsible for the hereditary inflammatory diseases FMF, Familial Cold Urticaria (FCAS), Muckle-Wells Syndrome (MWS), Hyperimmunoglobulinemia D with periodic fever syndrome (HIDS), TNF-receptor associated periodic syndromes (TRAPS), Neonatal-onset inflammatory disease/ chronic infantile neurologic cutaneous and articular syndrome (NOMID/CINCA) and Pyogenic arthritis with pyoderma gangrenosum and acne (PAPA). [76][77][78][79] All of these are characterized by recurrent febrile episodes with various constellations of clinical features. AA amyloidosis is common in FMF, rare in HIDS, uncommon in FCAS, present in about 10% of cases of TRAPS, and 25% of MWS.…”
Section: Amyloidoses Derived From Molecules Involved In Immune Functionmentioning
confidence: 99%
“…The relationship of this gene to intrinsic inflammatory processes is unclear. 77,78,[80][81][82][83] The prototypic and most frequently described of these disorders, FMF is autosomal recessive as is HIDS. The others appear to have dominant inheritance.…”
Section: Amyloidoses Derived From Molecules Involved In Immune Functionmentioning
confidence: 99%